Evaluation of ChatGPT in Solving the Illustration Exams of the 2023 Vietnamese National High School Graduation Exam - Đào Xuân Quy; Ngô Bắc Biển; Phan Xuân Dũng; Lê Ngọc Bích (Journal of Technical Education Science, 2024)
This article presents the results of ChatGPT (Feb 13 version) in solving the illustration exams for the 2023 Vietnamese National High School Graduation Exam, released by the Ministry of Education and Training in Vietnam. ChatGPT was tested for the nine subjects, including Mathematics, Literature, English, Physics, Chemistry, Biology, History, Geography, and Civic Education. The results show that ChatGPT can pass the illustration essay in both natural science and social science combinations. For multiple-choice questions, ChatGPT achieved scores of 5.4, 5.75, 4.75, 6.00, 7.75, 6.75, 7.75, and 7.80 in Mathematics, Physics, Chemistry, Biology, History, Geography, Civic Education, and English, respectively, and was found to be potentially of achieve a score of 6.47 in Literature. However, the results also demonstrate that ChatGPT’s scores in some subjects such as Mathematics, Physics, Chemistry, and Biology (scores 5-6) are lower than those in other subjects such as Literature, English, History, Geography, and Civic Education (scores 6-8). The data for ChatGPT’s questions and answers have been publicly released. It is anticipated that ChatGPT possesses the requisite capabilities to successfully pass the 2023 Vietnamese National High School Graduation Examination.